2022
DOI: 10.3390/ma15144850
|View full text |Cite
|
Sign up to set email alerts
|

Disinfection and Biocompatibility of Titanium Surfaces Treated with Glycine Powder Airflow and Triple Antibiotic Mixture: An In Vitro Study

Abstract: The aim of this in vitro study was to compare three disinfection protocols of biofilm-coated machined (MAC) and acid etched (SLA) commercial pure Grade 4 Titanium disks. Samples were infected with a vial of polymicrobial biofilm to simulate peri-implantitis in vitro. Seventeen MAC and twenty SLA titanium disks were randomly assigned to: (1) glycine powder air-flow (GYPAP) for 1 min; (2) a local delivered triple paste antibiotic composed by a gel mixture with ciprofloxacin, metronidazole, and clarithromycin (3M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 47 publications
2
19
0
Order By: Relevance
“…Abutment material has shown to be able to affect the stability of peri-implant mucosa and crestal bone as well [ 19 ]. When selecting the materials for abutments, clear prerequisites are a proven biological compatibility for assuring long-term stability, together with optimal biomechanical and physical properties [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abutment material has shown to be able to affect the stability of peri-implant mucosa and crestal bone as well [ 19 ]. When selecting the materials for abutments, clear prerequisites are a proven biological compatibility for assuring long-term stability, together with optimal biomechanical and physical properties [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from gold, ceramic might also be considered as an alternative material for customized implant abutments. Nevertheless, there is a lack of evidence to support or refute the use of porcelain (including feldspatic) for this specific purpose, but some authors report the use of feldspatic ceramic as a valid coating material for veneers, with an acceptable soft tissues margin adaptation [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The particle jet system is a widely studied method, especially when using sodium bicarbonate particles [ 22 , 24 , 27 , 28 ] and glycine [ 13 , 14 , 21 , 22 , 23 , 25 , 27 , 28 , 29 , 30 ]. It has been found that when smaller particle sizes such as glycine (25 ÎŒm) or erythritol (14 ÎŒm) are used, the surface changes are not significant compared to sodium bicarbonate (40-65 ÎŒm), which has larger particle sizes and consequently higher abrasive power [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among the peri-implant therapeutic approaches, the most commonly used can be categorised into four groups: mechanical, chemical, antibiotic and laser [ 4 , 13 ]. A number of methods, such as titanium brushing, particle blasting and, more recently, the electrolytic approach, have shown good results in the decontamination of titanium surfaces, with each method having a different effect on the surface structure [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Biofilms are considered to be the initiating factor of peri-implantitis [ 31 ]. Scientists have conducted many studies to determine how to efficiently remove biofilms [ 32 , 33 , 34 ]. Preventing biofilm formation is the most important way to avoid peri-implantitis and implant failure [ 35 ].…”
Section: Introductionmentioning
confidence: 99%